2018
DOI: 10.1039/c7tb02551c
|View full text |Cite
|
Sign up to set email alerts
|

A pH-sensitive guar gum-grafted-lysine-β-cyclodextrin drug carrier for the controlled release of 5-flourouracil into cancer cells

Abstract: The physiological environment is a crucial factor in biomedical systems, which can be regulated with relative ease both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…The surface morphology and size of the particles synthesized via DES grafted manner is shown in Figure DES have shown in agglomerate shapes; and this shape is better in terms of stability because it consists of molecules related to the homogeneity in the image, a hypothesis supported by Figure A . Based on the SEM observation of DES grafted PGA image was shown in Figure B, the DES grafted PGA is completely changed shape from agglomerate to spherical.…”
Section: Resultsmentioning
confidence: 79%
“…The surface morphology and size of the particles synthesized via DES grafted manner is shown in Figure DES have shown in agglomerate shapes; and this shape is better in terms of stability because it consists of molecules related to the homogeneity in the image, a hypothesis supported by Figure A . Based on the SEM observation of DES grafted PGA image was shown in Figure B, the DES grafted PGA is completely changed shape from agglomerate to spherical.…”
Section: Resultsmentioning
confidence: 79%
“…The difference of the mass during this process was measured. A mass loss in the curves indicated that a degradation (or) phase change of the measured substance takes place . For pure theophylline, there was only one weight loss stage from 211‐294 °C, corresponding to its decomposition and pyrolysis process.…”
Section: Resultsmentioning
confidence: 99%
“…In one word, there is increasingly scientific evidences revealing the evil part of chemotherapy drugs in tumor treatment, including promotions of metastasis, proliferation, immune escape, and so on [1][2][3]. Therefore, to develop new treatment strategy including nanotechnology-based methodologies [4][5][6][7][8][9] for cancer has been under continuous investigation during the past a few years. One of the most highlighted progresses is the successful achievement of complete remission in clinical of B cell lymphoma after treated with chimeric antigen receptor (CAR) T cells [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%